The Ethical-Dialectic Relationship of Islam and Indonesia: Reviewing Ahmad Syafii Maarif’s Thought - Arifin, Syamsul; Abdeljelil, Moncef Ben; Mu’ammar, Muhammad Arfan; Yusuf, Muhammad (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
Ahmad Syafii Maarif—affectionately known as Buya Syafii—is one of the Indonesian leading Muslim intellectuals and is a well-known national figure. This article examines Maarif’s Islamic thought and his dialectical-ethical link between Islam, national identity, and humanity. Using an in-depth textual analysis of the primary sources and supported by selected secondary sources, this study attempts to reveal Maarif’s intellectual legacy. This study concludes that Maarif was a Muslim intellectual who developed the model of a religious and democratic state. He bases his main argument that Islam does not need to be placed in a ‘binary opposition’ to the political reality and the national consensus, i.e., Pancasila as the last stated entity evidently accommodates the teachings of the Qur’an. He insisted that the ethical principles of Pancasila, which are in line with Islam, should be absorbed into public life in order to bring forth the right nation and the right state. To him, Islam in Indonesia must thus manifest itself as an ‘ethical entity’ to become the basis for modern Indonesia. He also called Muslims in Indonesia and elsewhere to comprehend the universal moral message of the Qur’an which has a versatile and immutable reach.